Heterogeneous Capital, the Production Function and the Theory of Distribution - Garegnani, P. (Review of Economic Studies, 1970)
The notion of capital as a “factor of production”, on which the theories of production and distribution dominant since the latter part of the last century ultimately rely, has been the object of considerable discussion in recent years. As is well known, these theories had their origin in a reformulation in terms of homogeneous land and “intensive” margins, of the Malthusian theory of rent.